Land resources as a key factor in the development of metropolises - Stankevych, Andrii (Ways to Improve Construction Efficiency, 2024)
The article examines the role of land resources in the development of metropolises through the lens of management, economic, and environmental aspects. In particular, it emphasizes issues related to the limited availability of land, its redevelopment, and the rational use of land to ensure the sustainable development of urban areas. Special attention is given to land management challenges in the context of rapid urbanization, such as effective land ownership, land use organization, and mechanisms for stimulating investment in the development of land infrastructure. One of the key aspects is the relationship between the use of land resources and the socio-economic development of metropolises. Proper land resource management ensures balanced development, improves the quality of life for residents, and creates favorable conditions for business and investment. Issues such as environmental pollution, the reduction of green spaces, and changes in the ecological state of metropolises due to intensive urban development are important factors that require special measures to preserve natural areas and enhance environmental safety. The article also examines modern methods and strategies used to optimize land use in metropolises. Given the global trends of urbanization, the need for sustainable development of metropolises becomes particularly relevant, and effective land resource management plays a crucial role in ensuring a harmonious balance between economic, environmental, and social interests. Overall, the role of land resources in the development of metropolises is not only a technical and economic issue but also a complex social problem that requires a comprehensive approach and effective management. The successful use of land resources can serve as the foundation for creating a comfortable, safe, and sustainable environment for the residents of metropolises, meeting their needs for housing, services, and infrastructure. To ensure the optimal use of limited land resources in metropolises, while preserving ecological balance and improving the quality of life for residents, it is essential to implement innovative and effective land management approaches. A sustainable approach to land management implies that all types of land use (residential, commercial, industrial, recreational, etc.) should be carried out in a way that minimizes ecological risks and ensures a balanced use of resources.